The Development of Balaghah Studies During The Dynamic of Studies (A Historical Glimpse into The Theory of Arabic Literature)/ منهجيّة و الدّراسات البلاغيّة في مرحلة الازدهار (لمحة تاريخيّة في نظرية الأدب العربيّ) - Farohidy, Atiq (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2021)
The purpose of this research is to determine the historical process of Balaghah studies which is taking place at the stage of the development of scientific dynamics and the study of Balaghah studies. This research is qualitative research and it uses the literature review method in the process of collecting data. The result of this study indicates that at the end of the second century of Hijriyyah, the Mufassirs had an enormous contribution to the growth and practice of developing Balaghah studies. In this century, Balaghah studies have revealed some of the knowledge of Tafsir and it has contributed adequately to understanding and revealing the verses of the Qur'an (I'jazul Qur'an). Then Balaghah studies reached the peak of the glory in the fourth century of Hijriyyah, specifically during the time of Abu Bakr Abdul Qahir al-Jurjani (W.471 H) with his construction theory text (Nazhariyah al-Nazhm) which was found in Dalailul I'jaz and at the same time, it became the basis for the formation of Ma’ani studies. He formulated the studies in detail about Bayan studies in his book "Asrar al-Balaghah". Furthermore, Al-Zamakhsyari (W.538 H) through his book "Tafsir al-Kasysyaf" has also a significant contribution to the progress of Balaghah studies.